HUBUNGAN ANTARA KEBIASAAN MEMBACA DENGAN TINGKAT LITERASI MEMBACA PEMAHAMAN SISWA KELAS IV DAN V DI UPT SPF SD INPRES MACCINI SOMBALA 1 - Iman Nur Iman; Hotimah; Rahmat Darmawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the relationship between reading habits and students’ reading comprehension literacy among fourth and fifth grade students at UPT SPF SD Inpres Maccini Sombala 1, Makassar. The background of this research is the low level of reading habits and reading comprehension literacy among students in Indonesia, which remains a major challenge in primary education. This study employed a quantitative approach with a correlational research design. The sample consisted of 104 students selected using a saturated sampling technique. Data were collected through a reading habits questionnaire and a reading comprehension literacy test. The data were analyzed using descriptive statistics and Pearson correlation analysis. The results showed that students’ reading habits were mostly in the moderate category, with an average score of 56.577, while their reading comprehension literacy was in the fair category, with an average score of 62.298. The correlation test revealed a correlation coefficient of 0.128 with a significance value of 0.196 (p > 0.05), indicating that there is no significant relationship between reading habits and reading comprehension literacy. These findings suggest that reading comprehension literacy is influenced not only by reading habits but also by other factors that need to be further investigated.